Risk Analysis and Risk Response in the Implementation of the Construction of a Special Oncology Hospital in Bojonegoro - Rahayuningsih, Titin; Nugroho, Laksono Djoko; Muhammadun, Haris (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
This study aims to identify risks, conduct risk analysis with the severity index method, and determine responses to risks that occur in the implementation of the Bojonegoro Regency Oncology Special Hospital Phase 2 construction work. From the results of risk identification, there are 31 risks grouped into 8 variables. After analysing the data with the severity index method, which is a technique used in calculating the probability value and also the impact, the results obtained were 3 risks in the medium category and 2 risks in the high category. The 5 dominant risks require a risk response. Risk responses to reduce the negative impact of project delays, especially for risks in the high category, include the risk of uncertain weather by planning the scheduling of large works such as casting so that they are not carried out during the rainy season. The risk of unavailability of labour in the field by cooperating with other subcontractors to help complete certain parts of the project.